Comparison of the Uptake Percentage of Technetium-99m Pertechnetate in Hyperthyroid Patients during Gamma Scintigraphy Examination - Wilson Soetanto; Robi Dany Riupassa (Jurnal Fisika, 2024)
Gamma scintigraphy is an examination that can be used to evaluate patients suspected of suffering from hyperthyroidism. This procedure involves administering the radiopharmaceutical Technetium-99m to the patient, followed by imaging using a gamma camera to check the function of the thyroid gland. The resulting image can be analysed using the ROI (Region of Interest) method to measure the percentage of radiopharmaceutical uptake by the thyroid. The aim of this study was to compare the uptake of radiopharmaceuticals in hyperthyroid patients and determine the correlation between uptake values and age and gender factors. This study involved 47 hyperthyroid patients, including 15 men and 32 women, aged between 10 and 75 years. The results showed that the average level of absorption (uptake) of radiopharmaceuticals by the right lobe of the thyroid (7.49% ± 7.41%) was higher than that by the left lobe (6.58% ± 6.31%). Additionally, men showed a higher uptake percentage (17.55% ± 14.34%) compared to women (12.44% ± 12.86%). Another finding was that there was a significant (strong) negative correlation between the uptake value and the patient's age, both in men (r = -0.641, p = 0.00988) and women (r = -0.674, p = 0.00010).